Tophaceous gout causing atlanto-axial subluxation mimicking rheumatoid arthritis: a case report. - Wazir, N.N.; Moorthy, V.; Amalourde, A.; Lim, H.H. (2005)
This is a case report of an extremely rare condition of atlanto-axial subluxation secondary to gouty arthritis, which mimicked rheumatoid arthritis at presentation. Gouty arthritis involving the spine is a rare condition. We highlight a case of gouty arthritis involving the atlanto-axial joint resulting in joint instability, subluxation, and neurological deficit. A 66-year-old obese woman who had a polyarticular disease for the previous 3 years presented with neck pain and progressive neurology. A 2-stage procedure was performed: posterior decompression and occipitocervical fusion followed by further anterior trans-oral decompression. However, after an initial neurological improvement, she succumbed to aspirational pneumonia and septicaemia. Atlanto-axial subluxation caused by gouty arthritis can present in the same way as rheumatoid arthritis. Therefore, the possibility of this as a differential diagnosis should be kept in mind.